Pediatric liver transplantation in Australia and New Zealand: The case for a collaborative anesthetic database. Issue 3 (3rd December 2020) - Paterson, Neil A. B.; Lee‐Archer, Paul; Shirley, Anna; Lee, Julie
Abstract: Background: Liver transplantation is conducted with strict oversight of organizational structure and clinical practice. However, specific regulations pertaining to the delivery of anesthetic services are lacking and consideration of departmental structure and mechanisms for quality control must occur at a local level. Busy centers collect and process sufficient data to guide this process but those with low case loads may not generate enough data for useful analysis. In Australia and New Zealand, pediatric liver transplants are performed at only four locations. As these operations are not equally distributed geographically or temporally there are periods of low activity at some centers. As anesthesia affects patient outcome, quality assurance activities are important in this setting. Aims: Provide a global overview of the structure and function of liver transplantation networks. Identify issues related to provision of pediatric anesthetic services with specific reference to Australasia. Examine anesthetic data from a single pediatric center to illustrate benefits and limitations of such activity. Methods: Pediatric liver transplant centers from Australia and New Zealand were surveyed to determine the organizational and logistical issues related to a liver transplant service. An audit of 15 years of liver transplants from a single center was conducted for benchmarking purposes and to identify changes in anesthetic practice over time. Results: Pediatric liver transplants performed in Queensland from January 2005 to December 2019 were reviewed. Changes in transfusion practice reflected international trends. Morbidity and mortality were comparable to international data. Important complications such as hepatic artery and portal vein thrombosis were uncommon and did not generate enough data for further analysis. Conclusions: Combining the anesthetic liver transplant data from all sites in a single registry would expand data collection and generate broadly applicable findings. We propose the establishment of an Australasian pediatric anesthetic liver transplant database.